Regulation of Colonic Inflammation and Macrophage Homeostasis of IFN-γ-Primed Canine AMSCs in Experimental Colitis in Mice - Chan-Hee Jo; Sang-Yun Lee; Young-Bum Son; Won-Jae Lee; Yong-Ho Choe; Hyeon-Jeong Lee; Seong-Ju Oh; Tae-Seok Kim; Chae-Yeon Hong; Sung-Lim Lee; Gyu-Jin Rho (Animals)
Mesenchymal stem cells (MSCs) have shown potential in treating immune-mediated diseases due to their immunomodulatory properties, which can be enhanced by priming with inflammatory cytokines like interferon-gamma (IFN-γ). This study evaluates the therapeutic effects of IFN-γ-primed canine adipose tissue-derived MSCs (AMSCs) in a mouse model of inflammatory bowel disease (IBD). Canine AMSCs were primed with 50 ng/mL recombinant canine IFN-γ for 48 h, and the effects were compared to those seen in naïve (unprimed) AMSCs. IBD was induced in mice using dextran sodium sulfate (DSS), and AMSCs were injected intraperitoneally on days 1 and 3. The mice treated with IFN-γ-primed AMSCs showed improved clinical outcomes, including a reduced disease activity index (DAI), less body weight loss, and longer colon length compared to the mice treated with naïve AMSCs. A histological analysis revealed less damage to the intestinal structures and reduced inflammatory cell infiltration. IFN-γ priming led to a shift in the immune cell balance in the gut, decreasing pro-inflammatory macrophages (Ly6Chi) and increasing anti-inflammatory macrophages (Ly6Clo/MHC-IIhi). This was associated with the reduced expression of inflammatory cytokine genes (Il-1β, Il-6, and Il-18) and increased expression of the intestinal stem cell marker Lgr5. These findings suggest that IFN-γ-primed AMSCs offer enhanced therapeutic potential for treating CE in veterinary medicine.